Decreased Bone Type I Collagen in the Early Stages of Chronic Obstructive Pulmonary Disease (COPD). (2nd September 2020) - Junqueira, Jader Joel Machado; Lourenço, Juliana Dias; da Silva, Kaique Rodrigues; Cervilha, Daniela Aparecida de Brito; da Silveira, Lizandre Keren Ramos; Correia, Aristides Tadeu; Silva, Larissa Emidio de França; Teodoro, Walcy Rosolia; Tibério, Iolanda de Fátima Lopes Calvo; Barbosa, Alexandre Póvoa; Lopes, Fernanda Degobbi Tenorio Quirino dos Santos
Abstract: Smoking is the main risk factor for the development of chronic obstructive pulmonary disease (COPD) and is known to have deleterious effects on bone metabolism. However, the effects on bone collagen matrix during the development of COPD are unclear. The aim of this study was to evaluate the temporal effect of cigarette smoke exposure on bone type I collagen during COPD development in a cigarette smoke-induced model. C57BL/6 mice were allocated to three groups: control (C), animals exposed to filtered air for 1, 3 and 6 months; cigarette smoke (S), animals exposed to cigarette smoke for 1, 3 and 6 months; provisional smoking (PS), animals exposed to cigarette smoke for 3 months, followed by another 3 months of filtered air exposure. Evaluation of the respiratory mechanics and alveolar enlargement were performed. Femoral and tibial extraction was also performed to evaluate the type I collagen by immunofluorescence and COL1A1 gene expression. Exposure to cigarette smoke led to an alveolar enlargement and progressive reduction in lung tissue resistance and elastance, progressive reduction of type I collagen and reduction in COL1A1 gene expression. Although we did not observe any improvement in the functional and histological parameters in the provisional smoking group, we detected an increase in COL1A1 gene expression. A worsening in bone collagen matrix is part of the initial physiopathological events during COPD development and the smoking cessation induced an evident recovery of COL1A1 expression, possibly to attempt at tissue repair.